Dolph Algebras and Dolph Groups (Selecciones Matemáticas, 2023)
A finite Hopf crossed product whose base ring is a finite field will be called a Dolph algebra, and the corresponding group of units will be called a Dolph group. Assuming known the crossed product of a ring and a group under a crossed mapping [1], the units of the cross products Z2[X] ⟨X2⟩ ⋊f C2 and Z3[X] ⟨X2⟩ ⋊f C2 are calculated. Furthermore, we give concrete examples of 4 classes of Hopf crossed products.
Keywords: Finite groups; crossed products; 2-cocycle; group of units; Dolph algebras